Pengelolaan Krisis dalam MSDM : Tanggapan Human Resources terhadap Tantangan Pasca Pandemi(Studi Kasus di Balai Desa Jombang) - Masyhudi Masyhudi; Nugroho Edie Santoso; Hanif Hadinata Utama (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to analyze the human resource (HR) management strategies employed by the Jombang Village Hall in addressing post-pandemic challenges, including the implementation of flexible work practices, improving employee welfare, and digital transformation. The research method used was descriptive qualitative with a case study approach, using in-depth interviews, participant observation, and documentation analysis. The results indicate that HR plays a strategic role as an agent of change by implementing a hybrid work policy, providing psychosocial support through internal communication and counseling, and conducting digital training to improve the competency of village officials. The findings also indicate that obstacles such as limited technological infrastructure, resistance to change, and psychological stress impact the effectiveness of HR management. The conclusion of this study confirms that post-pandemic HR management at the Jombang Village Hall requires a holistic and adaptive approach, integrating flexible work practices, employee welfare, and digital transformation to support village official performance and the quality of public services.   Keywords: HR Management, Crisis, Post-Pandemic, Human Resources, Village Government